Nature as Witness: Environmental Forensics and Scientific Responses to Ecological Crime - Nandini Singh (AG Volumes, 2026)
Environmental crimes are grave threats to the ecosystem, biodiversity, public health and sustainable development and require strong scientific methods to investigate and prevent. Environmental forensics has become an interdisciplinary science that brings together chemistry, biology, geology, toxicology, molecular science and geospatial technologies to determine sources, characterize and track environmental contaminants, and provide legally defensible evidence. This review addresses the concept of the "Nature as Witness" focusing on the natural elements that include soil, water, air, sediments, vegetation and wildlife, which maintain physical, chemical and biological evidence of disturbances to the environment. The paper addresses pollution investigations, illegal mining, investigations of wildlife crime, oil spills, and plastic contamination investigations, as they relate to environmental crime scene investigation and evidence collection, as well as some of the analytical processes used, such as chemical fingerprinting, stable isotope analysis, environmental DNA, chromatography, spectroscopy, and remote sensing. It also emphasises on legal, regulatory and scientific problems in the Indian scenario and discusses new technologies like Artificial Intelligence, IoT-based monitoring, portable forensic instruments and climate forensics. The review highlights that the adoption of cutting-edge scientific approaches alongside good environmental governance measures can reinforce environmental justice, enhance environmental criminal investigations, and facilitate sustainable natural resource conservation.